Design and Development of Power Monitoring System using IoT Technology - Sanjeev Joshi, Dr. Kiran V (International Journal of Advanced Science and Technology, 2020)
Abstract A Hardware for a high speed Energy-Monitoring device is designed and a firmware is developed, which captures the power parameters such as voltage, current, frequency, power factor, Active power, Reactive power and apparent power in 10 milliseconds and sends the data via USB in 200ms to Raspberry Pi, where a python script runs which further sends the data to cloud for real time monitoring. The hardware is designed using Orcad and Allegro software and the firmware was developed in Keil uVision IDE. STM Microcontroller was used as the controller and drivers for Energy Meter Chip was used for development of firmware. The mode of communication between the microcontroller and the energy meter chip is SPI and hardware is connected with Raspberry Pi module via USB which further runs script to collect the data. Thingspeak cloud was used for Real-Time monitoring of the data on the cloud. In the cloud, the user can monitor the power parameters at an interval of 1 sec for one each data as a part of result. User can also collect the data from the cloud and do analysis by giving the data as an input for an algorithm which in turn predicts power signatures of the appliance and identifies the type of appliance connected and informs the user about it.